Comprehending Leadership Patterns with focus on Servant Leadership - Manodip Ray Chaudhuri (Jurnal Manajemen Indonesia, 2021)
Leadership is the art of motivating a group of people to act towards achieving a specific goal. Leadership style is the method and approach of providing direction, implementing plans and motivating people. It is the sum total of explicit and implicit actions performed by the leader. The study investigates the different leadership styles in the organisation and a country wise classification of how leadership style varies across different nations. This is on the basis of factors like power distance, equality and decision making process. This paper also touches upon certain dark aspects of leadership. The method of collecting data constitutes of primary and secondary research. Primary research has been done by the way of unstructured face to face interview, telephonic interview and interview through emails, while secondary research includes books, journals, articles, magazines and online blogs.